2017
DOI: 10.1038/s41598-017-04601-z
|View full text |Cite|
|
Sign up to set email alerts
|

Pancreatic cancer: Circulating Tumor Cells and Primary Tumors show Heterogeneous KRAS Mutations

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a devastating disease. Circulating tumor cells (CTC) in the blood are hypothesized as the means of systemic tumor spread. Blood obtained from healthy donors and patients with PDAC was therefore subject to size-based CTC-isolation. We additionally compared Kirsten rat sarcoma viral oncogene homolog (KRAS) mutations in pancreatic CTC and corresponding tumors, and evaluated their significance as prognostic markers. Samples from 68 individuals (58 PDAC patients, 10 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 56 publications
6
74
0
Order By: Relevance
“…47 They were able to demonstrate that patients with MUC-1eexpressing CTCs (n Z 10) had a shorter median OS (2.7 months), compared with those with MUC-1enegative CTCs (n Z 13; 9.6 months). Kulemann et al 29 looked at KRAS mutation subtypes in CTCs from 58 PDAC patients. Those with a KRAS G12V mutation (n Z 14) had a better OS (24.5 months) compared to those with other (10 months) or no detectable KRAS mutations (8 months; P Z 0.04).…”
Section: Ctc Detection In Pancreatic Cancermentioning
confidence: 99%
“…47 They were able to demonstrate that patients with MUC-1eexpressing CTCs (n Z 10) had a shorter median OS (2.7 months), compared with those with MUC-1enegative CTCs (n Z 13; 9.6 months). Kulemann et al 29 looked at KRAS mutation subtypes in CTCs from 58 PDAC patients. Those with a KRAS G12V mutation (n Z 14) had a better OS (24.5 months) compared to those with other (10 months) or no detectable KRAS mutations (8 months; P Z 0.04).…”
Section: Ctc Detection In Pancreatic Cancermentioning
confidence: 99%
“…Insofar as the commonly used anti-RAS antibodies do not differentiate between RAS protein isoforms it may be that suppression of KRAS mut expression relieves the negative feedback KRAS mut →NRAS (and, possibly, both HRAS and NRAS) pathway[s] [ 40 ] thereby stabilizing total RAS expression. Other potentially contributory mechanisms to consider are 1) differences between studies in procedures and xenograft genotypes/phenotypes and their derivative signaling pathways [ 41 ], 2) the presence of extensive intratumoral heterogeneity as seen in recent CTC single cell expression data [ 42 ], 3) a lower KRAS mut ratio [ 43 ], 4) a KRAS mut effect on stem cell distribution (which would also account for epithelial-mesenchymal (EMT) shift) [ 44 , 45 ], and 5) the stochastic, non-determinant loss of KRAS mut stem cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lymph‐node involvement does not accurately predict the haematogenous dissemination of cancer cells, nor is haematogenous dissemination necessarily associated with lymph‐node involvement . Although the routine detection of CTCs has not been recommended as a prognostic method, numerous studies have demonstrated that the number of CTCs per mL is associated with the median overall survival . Hundreds of clinical trials incorporating CTC count as a biomarker in patients with various types of solid tumours are ongoing .…”
Section: Dtc In Bone Marrow May Be a Prognostic Biomarker For Relapsementioning
confidence: 99%
“…59 Although the routine detection of CTCs has not been recommended as a prognostic method, numerous studies have demonstrated that the number of CTCs per mL is associated with the median overall survival. 107 Hundreds of clinical trials incorporating CTC count as a biomarker in patients with various types of solid tumours are ongoing. 108 CTCs thresholds range from 1 to 5 per mL for prognostic value in various cancer types, and the range for DTCs in the bone marrow is 1-2 per 2 × 10 6 cells.…”
Section: Dtc In Bone Marrow May Be a Pr Ognostic Biomarke R For Relmentioning
confidence: 99%